Deep lenses of circumpolar water in the Argentine Basin - art. no. 3007 - Arhan, Michel; Carton, Xavier; Piola, A; Zenk, W (Journal of Geophysical Research, 2002)
[1] Three deep anticyclonic eddies of a species only reported once before [Gordon and Greengrove, 1986] were intersected by hydrographic lines of the World Ocean Circulation Experiment (WOCE) and South Atlantic Ventilation Experiment (SAVE) programs in the Argentine Basin. The vortices are centered near 3500 m depth at the interface between North Atlantic Deep Water and Bottom Water. They have similar to1500-m-thick cores containing Lower Circumpolar Deep Water and a dynamical influence that may span up to two thirds of the water column. As one eddy was observed just downstream of the western termination of the Falkland Escarpment, a destabilization of the deep boundary current by the sudden slope relaxation is suggested as a potential cause of eddy formation. Besides isopycnal interleaving at the eddy perimeters, strongly eroded core properties in the upper parts of the lenses, associated with low density ratios, hint at double diffusion at the top of the structures as another major decay mechanism. The presence of an eddy in the northern Argentine Basin shows the possibility for a northward drift of the vortices, in this basin at least. Deep events in recent current measurements from the Vema Channel are presented that raise the question of further equatorward motion to the Brazil Basin.